Melodías de Colombia y Latinoamérica: Un recorrido entre cuerdas y arcos (2023)
The selection of the works proposed in this publication seeks to contribute to music education from the violinist exercise, conceived from a technical and interpretative point of view that recognizes the diversity of resources that the instrument allows to interpret traditional music.